Training Model Design Terrarium to Increase Teachers Special Education Competency - Asriwijiastuti; Masitoh, Siti; Ardianingsih, Febrita (Jurnal Pedagogi dan Pembelajaran, 2024)
Special education teachers with non-science backgrounds were found to have 85% below standard and weak competency in explaining environmental phenomena related to ecosystem concepts and experiments. This condition requires conscious efforts to enhance quality through modeling and direct experimentation. This study aims to analyze the improvement of teacher competencies in creating terrariums by applying a training model based on "Gagne’s nine events of instruction". The method used is a pre-post design, data collection using test methods, and analyzed using the Wilcoxon test with SPSS 26. This research was conducted on 21 teachers from SLB School. The competency results of teacher knowledge based on the pretest and posttest show t count = 11.370 and t count = 3.092, t table (10-1) with alpha 0.05 two-tail = 1.833. Thus, the application of the training model based on Gagne's learning perspective improves teacher competencies in teaching terrarium materials. Furthermore, the training model can provide basic vocational knowledge, especially in terrarium design, improve teacher mastery, and motivation. The implications of this research can be used in schools with limited space to be presented in the classroom through mini-labs in the form of terrariums and for teachers teaching students with intellectual disabilities. These findings can serve as a reference for teachers in special education to conduct meaningful learning for students with intellectual disabilities in other learning materials.